Effects of Standardized Ileal Digestible Lysine on Growth Performance and Economic Return of 200 to 300 lb Grow-Finish Pigs - Larissa L. Becker; Emily E Scholtz; Joel M DeRouchey; Mike D. Tokach; Jason C. Woodworth; Robert D. Goodband; Jordan T. Gebhardt; Jon A. De Jong; Fangzhou Wu; Kiah M. Gourley; Joe P. Ward; Casey R. Neill (Kansas Agricultural Experiment Station Research Reports, 2021)
A total of 2,099 barrows and gilts (PIC 1050 × DNA 600; initially 198.6 ± 3.72 lb) were used in a 57-d study to determine the optimal dietary standardized ileal digestible (SID) Lys level for approximately 200 to 300 lb pigs in a commercial setting. Pigs were randomly allotted to 1 of 4 dietary treatments with 24 to 27 pigs per pen and 20 replications per treatment. A similar number of barrows and gilts were placed in each pen. Diets were fed over 2 phases (199 to 233 and 233 to 299 lb respectively). Dietary treatments were corn-soybean meal-based. Diets were formulated to 85, 93, 100, or 110% of the 2016 PIC (Hendersonville, TN) SID Lys gilt recommendations with phase 1 SID Lys levels of 0.65, 0.71, 0.77, 0.84%, and phase 2 levels of 0.60, 0.66, 0.71, 0.78%, respectively. Overall (d 0 to 57), increasing SID Lys increased (linear,P<0.05) overall market weight, F/G, hot carcass weight, Lys intake/d, and Lys intake/kg of gain with an increase in ADG (quadratic,P= 0.020). For economics (d 0 to 57), feed cost per lb of gain increased (linear,P<0.05) with increased SID Lys. Revenue per pig placed and income over feed cost (IOFC) increased (quadratic,P<0.10) as the amount of SID Lys increased, and marginally significant evidence of a quadratic response for feed cost per pig placed (P= 0.073). Projecting IOFC for phase 1, the quadratic polynomial (QP) and broken-line linear models estimated the requirement at 110.9% and 96.9%, respectively, to achieve maximum IOFC. For phase 2, the QP estimated the requirement at 96.6% SID Lys to maximize IOFC. In summary, the SID Lys requirement was 97% to 111% of the 2016 PIC recommended Lys requirement for phase 1 and 97% for phase 2 to maximize IOFC.
Keywords: finishing pig; lysine requirement; economics